2002
DOI: 10.1046/j.1439-0523.2002.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to race F of broomrape in sunflower lines of different origins

Abstract: A new race F of broomrape overcomes all known resistance genes in cultivated sunflower, but recently, sources of resistance against race F have been developed. The objective of the present research was to study the inheritance of resistance to race F in crosses between 12 resistant sunflower breeding lines, derived from three different sources of resistance, and the susceptible male-sterile line P-21. Parental lines and F 1 , F 2 , F 3 and BC 1 generations were evaluated for broomrape resistance. Segregations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 4 publications
3
37
1
Order By: Relevance
“…Resistance to this new race has been found in both cultivated and wild sunflower (Domínguez 1999;Sukno et al 1999;Fernµndez-Martínez et al 2000;Jan et al 2002). Resistance to race F of broomrape in germplasm derived from cultivated sunflower has been reported to be recessive and controlled by alleles at two loci (Rodríguez-Ojeda et al 2001;Akhtouch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to this new race has been found in both cultivated and wild sunflower (Domínguez 1999;Sukno et al 1999;Fernµndez-Martínez et al 2000;Jan et al 2002). Resistance to race F of broomrape in germplasm derived from cultivated sunflower has been reported to be recessive and controlled by alleles at two loci (Rodríguez-Ojeda et al 2001;Akhtouch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Most genetic studies on different resistance sources to races A through E concluded that a major dominant gene conferred resistance to the latest race and to the previous ones (Vrânceanu et al, 1980;Sukno et al, 1999), even though other genetic mechanisms such as two dominant genes were also reported (Domínguez, 1996b). In contrast to races A though E, initial genetic studies on resistance to race F concluded the presence of recessive alleles at two independent loci named Or 6 and Or 7 (Rodríguez-Ojeda et al, 2001;Akhtouch et al, 2002). Contrarily, Pérez-Vich et al (2002) found that resistance to race F in sunflower line J1 derived from wild species was controlled by dominant alleles at a single gene designated Or 6 .…”
Section: Characterization Of Resistancementioning
confidence: 99%
“…b NK: not known; the parasite was reported, but no information about race/s is known. Vrânceanu et al (1980), Akhtouch et al (2002), Pacureanu et al (2004), andPérez-Vich et al (2004).…”
mentioning
confidence: 98%
“…proved to be a major reservoir of resistance genes against O. cumana race F (Fernández-Martínez et al, 2000), and some of them were incorporated into cultivated sunflower through interspecific hybridization (Jan & Fernández-Martínez, 2002). Resistance to race F from Spain found in the lines KI-534 and P-96, derived from cultivated germplasm, was controlled by recessive alleles at two loci (Rodriguez-Ojeda et al, 2001;Akhtouch et al, 2002), the same recessive genes controlling resistance to race E in the line KI-534 (Rodriguez-Ojeda et al, 2001). Contrarily, resistance to this race from Spain in line J1, derived from interspecific crosses, and to race F from Romania in line LC1093 was found to be mainly dominant and controlled in J1 by the Or 6 gene, with incomplete dominance, and Or 7 , whose expression was influenced by the environment (Velasco et al, 2007), and in LC1093 by Or 6 (Pacureanu-Joita et al, 2004) (Table 2).…”
mentioning
confidence: 99%